Research on the method of weight calculation and equipment arrangement optimization of tramcar - DUAN Huadong; LIU Xiaofeng; JIANG Zhongcheng; ZHANG Bo (机车电传动)
Research was carried out on the weight calculation and equipment layout optimization methods of five-module articulated floating tram. According to the material mechanics method, a tram weight calculation method was proposed. Compared with the calculated results based on FE finite element model, the error was less than 4%, which proved that the weight calculation accuracy was high. Based on Isight optimization platform, multi-objective optimization algorithm was adopted to improve the equipment layout. Because of its low optimization efficiency and only searching the local optimal solution, the mixed integer linear programming algorithm was finally proposed to develop the tram equipment layout optimization model. The optimization model comprehensively considered various constraints such as equipment interference, equipment clearance, maintenance space and equipment binding to search the global optimal solution, so as to greatly improve the efficiency of equipment layout optimization, and the axle and wheel weight deviation were optimized to 0 in the state of reconditioning. Based on the equipment layout parameters in the state of reconditioning, the wheel weight deviations were less than 1.5% in the conditions of full seat, load and overweight. The accuracy and efficiency of the method can meet the needs of engineering applications.